1991
DOI: 10.1093/infdis/163.3.579
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor Enhances the Phagocytic and Bactericidal Activity of Normal and Defective Human Neutrophils

Abstract: Granulocyte colony-stimulating factor (G-CSF) stimulates proliferation of myeloid cells and may be a valuable adjunct in prevention and treatment of neutropenia-associated infections. Neutrophil (PMNL) phagocytic and microbicidal functions against Staphylococcus aureus and Candida albicans blastoconidia were therefore evaluated. Bacterial phagocytosis and bactericidal activity were significantly enhanced by approximately 50%-70% after preincubation of normal PMNL with G-CSF in concentrations of 1000-4000 units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
143
5
6

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(158 citation statements)
references
References 22 publications
4
143
5
6
Order By: Relevance
“…In vitro studies have highlighted the priming effects of G-CSF on the antimicrobial activity of neutrophils [15,18,37,38]. In vivo experimental animal models have also described a protective effect of G-CSF administration [39±41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have highlighted the priming effects of G-CSF on the antimicrobial activity of neutrophils [15,18,37,38]. In vivo experimental animal models have also described a protective effect of G-CSF administration [39±41].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, neutrophil depletion in immunocompetent mice increased susceptibility to M. avium infection [12]. In patients with AIDS, neutrophil function is impaired [13±15] while neutropenia can be found associated with HIV infection, representing a risk for the development of infection [16,17] Recombinant human granulocyte-colony stimulating factor (rHuG-CSF) was shown to improve the neutrophil function defects in these patients, namely by improving their microbicidal activity [15,18]. Newman et al [19] have shown that neutrophils from AIDS patients significantly inhibited M. avium growth after administration of rHuG-CSF ex vivo.…”
Section: Disseminated Infection By Mycobacterium Avium Complex (Mac)mentioning
confidence: 99%
“…It can also mobilize progenitor cells from the bone marrow into peripheral blood that can be used for hematopoietic reconstitution (Molineux et al, 1990;Bensinger et al, 1995;Schmitz et al, 1995). In addition to its role in the regulation of granulopoiesis, G-CSF enhances functions of mature neutrophils such as phagocytosis (Roilides et al, 1991), respiratory burst (Sullivan et al, 1993) and microbicidal activity (Vechiarelli et al, 1995). G-CSF has been shown to facilitate the clinical recovery of the nonneutropenic host in several animal models of infection (Dale et al, 1995) and in clinical trials of non-neutropenic patients with pneumonia (Welte et al, 1996).…”
mentioning
confidence: 99%
“…Rh-GCSF acts on granulocytopoietic progenitor cells to stimulate clonal proliferation of neutrophils, and it also improves neutrophil adhesion, chemotaxis, and phagocytic activity. [13][14][15] An international registry established to monitor the progress of patients who have SCN and are treated with rh-GCSF recently reported data collected on 853 patients. 1 The data show that 92.1% of patients respond to rh-GCSF at doses Ͻ30 g/kg per day.…”
Section: Discussionmentioning
confidence: 99%